Caryological study of quercus humboldtii bonpl (1989)
Using lactopropionic orceine for a previus tintion we obtained the Caryotype and ideogram of Quercus humboldtii Bonpl. and we observed that it has 2 n = 24 chromosomes as most studied species of Quercus do.